Undergraduate Awareness and Utilization of Simulation for Learning - Aderonke Kofo Soetan; Amos Ochayi Onojah; Benson Oluwatimilehin Nelson (Indonesian Journal of Multidiciplinary Research, 2023)
This study investigated undergraduate awareness and utilization of simulation for learning at the University of Ilorin. This study adopted descriptive research of the survey. 4 research questions were developed and answered.  The target population for the study was 239 undergraduate students of the University of Ilorin, which were randomly selected. The findings of the study were (i) undergraduates are aware of the utilization of simulation for learning at the University of Ilorin; (ii) simulation is often utilized for learning amongst undergraduates of the University of Ilorin; (iii) gender differences do exist between a male and female student on the utilization of simulation in among undergraduate of the University of Ilorin; and (iv) area of specialization does not influence the utilization of simulation for learning amongst the university of Ilorin undergraduate. The utilization of simulation for learning has enhanced various students learning capabilities, this has also increased interest amongst students in instructional content. This implies that simulation when properly utilized for learning can positively impact the performance of students. Therefore, efforts should be made to ensure availability and proper awareness of the utilization of simulation systems in various fields of study.